Musical theatre song a comprehensive course in selection, preparation and presentation for the modern performer - Purdy, Stephen (Performance books, 2016)
Theater Studies. Musical Theatre Song is a handbook for musical theatre performers, providing them with the wide-ranging skill set they need for success in today's competitive musical theatre environment. Breaking down the process into knowing how to select your song material based upon your individuality and how to prepare and perform it in a manner that best highlights your attributes, Stephen Purdy provides a succinct and personalized trajectory toward presentation, taking the reader through a series of challenges that is designed to evoke original, personal and vibrant song performances. Written by renowned Broadway and West End vocal and audition coach Stephen Purdy, Musical Theatre Song is a must-have guide for all performers who are looking to succeed in the musical theatre industry.